2023
DOI: 10.3892/mmr.2023.13090
|View full text |Cite
|
Sign up to set email alerts
|

Serum‑derived exosomal hsa‑let‑7b‑5p as a biomarker for predicting the severity of coronary stenosis in patients with coronary heart disease and hyperglycemia

Shufang Han,
Jie Fang,
Lili Yu
et al.

Abstract: Exosomal microRNAs (miRNAs/miRs) are potential biomarkers for the diagnosis and treatment of cardiovascular disease, and hyperglycemia serves an important role in the development of atherosclerosis. The present study aimed to investigate the expression profile of serum-derived exosomal miRNAs in coronary heart disease (CHD) with hyperglycemia, and to identify effective biomarkers for predicting coronary artery lesions. Serum samples were collected from eight patients with CHD and hyperglycemia and eight patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Previous studies have revealed the presence of small RNAs in blood and various body fluids ( 10 ). Serum miRNAs has been a potential biomarker in the diagnosis and prognosis of various diseases, including cancer ( 11-13 ), cardiovascular diseases ( 14 ) and neurodegenerative diseases ( 15 ). Researchers frequently use different protocols and kits to perform serum RNA extractions for miRNA analysis ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed the presence of small RNAs in blood and various body fluids ( 10 ). Serum miRNAs has been a potential biomarker in the diagnosis and prognosis of various diseases, including cancer ( 11-13 ), cardiovascular diseases ( 14 ) and neurodegenerative diseases ( 15 ). Researchers frequently use different protocols and kits to perform serum RNA extractions for miRNA analysis ( 16 ).…”
Section: Introductionmentioning
confidence: 99%